Ответ: ( -2 ; 3 )
Объяснение:
[tex] \left \{ \begin {array}{l} \dfrac{3-x}{5}+ \cfrac{5+y}{4} =3~~ \big | \cdot 20 \\\\\\ \dfrac{8+x}{3} - \dfrac{y-1}{2} = 1 ~~ \big |\cdot 6 \end{array}\right. \Leftrightarrow \left \{ \begin {array}{l} 4(3-x) + 5(5+y) = 60 \\\\ 2(x+8)-3(y-1) = 6 \end{array} \right. \Leftrightarrow \\\\\\ \Leftrightarrow \left \{ \begin {array}{l} 12- 4x + 25 +5y = 60 \\\\ 2x + 16 -3y +3 = 6 \end{array} \right. \Leftrightarrow \left \{ \begin {array}{l} 5y - 4x = 23 \\\\ 2x -3y = -13 \end{array} \right. \Leftrightarrow \\\\\\\ \Leftrightarrow \left \{ \begin {array}{l} 5y - 4x = 23 \\\\ 2x -3y = -13~~ \big |\cdot 2 \end{array} \right. \Leftrightarrow \oplus \left \{ \begin {array}{l} 5y - 4x = 23 \\\\ 4x -6y = -26 \end{array} \right. \\\\\\ -6y+5y+4x -4x = 23- 26 \\\\ -y = -3 \\\\ y =3 \\\\ x= (3y -13 ):2 =- 2 [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: ( -2 ; 3 )
Объяснение:
[tex] \left \{ \begin {array}{l} \dfrac{3-x}{5}+ \cfrac{5+y}{4} =3~~ \big | \cdot 20 \\\\\\ \dfrac{8+x}{3} - \dfrac{y-1}{2} = 1 ~~ \big |\cdot 6 \end{array}\right. \Leftrightarrow \left \{ \begin {array}{l} 4(3-x) + 5(5+y) = 60 \\\\ 2(x+8)-3(y-1) = 6 \end{array} \right. \Leftrightarrow \\\\\\ \Leftrightarrow \left \{ \begin {array}{l} 12- 4x + 25 +5y = 60 \\\\ 2x + 16 -3y +3 = 6 \end{array} \right. \Leftrightarrow \left \{ \begin {array}{l} 5y - 4x = 23 \\\\ 2x -3y = -13 \end{array} \right. \Leftrightarrow \\\\\\\ \Leftrightarrow \left \{ \begin {array}{l} 5y - 4x = 23 \\\\ 2x -3y = -13~~ \big |\cdot 2 \end{array} \right. \Leftrightarrow \oplus \left \{ \begin {array}{l} 5y - 4x = 23 \\\\ 4x -6y = -26 \end{array} \right. \\\\\\ -6y+5y+4x -4x = 23- 26 \\\\ -y = -3 \\\\ y =3 \\\\ x= (3y -13 ):2 =- 2 [/tex]